Bruce Bronzan Campaign Retreat at Morris Cabin-Shaver Lake - Watkins, Howard::::::::: (1978)
Christine Watkins, Doug Broten (backside), Bruce Bronzan, Linda Bronzan, ?, Raul Martinez, Sandy Walsh, Randy Walsh playing guitar, Dave Brodie in blue jeans